Działalność wydawnicza i graficzna Wiener Werkstätte jako przejaw ruchu artystycznego Arts and Crafts w europejskiej kulturze pierwszej połowy XX w. - Łakomy-Chłosta, Agnieszka (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
At the end of the 19th century, an artistic movement called Arts and Crafts emerged in Great Britain. Its premises were eagerly accepted both in other European countries and abroad, e.g., in the United States. One of the examples of workshops that identified with the ideas of this movement was the Wiener Werkstätte (Vienna Workshop). They were founded in Vienna in 1903 by Josef Hoffmann and Koloman Moser. They produced beautiful utilitarian objects designed by artists and made by high-class craftsmen. One of the aspects of Wiener Werkstätte’s activity regarded issuing publications and related graphic designs. The article discusses this area of the studio’s operation, pointing to examples of individual products.